A review of probiotics in shrimp aquaculture - van Hai, Ngo; Fotedar, Ravi (Food Products Press and Haworth Press Inc., 2010)
Development of shrimp aquaculture has been associated with increases in infectious diseases and environmental degradation. An effective alternative to chemicals and antibiotics used for the prevention of these problems is to administer probiotics into the rearing system. Three bacterial genera, Bacillus, Vibrio, and Pseudomonas, are commonly administered as probiotics in shrimp aquaculture. Candidate probiotics are species specific and need to be tested for their effectiveness for certain species in in vitro and in vivo. Supplementation into feed is more effective in conveying probiotics into animals compared to direct application into rearing systems. Overdosage or prolonged administration of probiotics can induce immunosuppression. A cell-density of 105 colony-forming units (CFU) per ml is widely recommended. A combination of probiotics results in better outcomes for the host than individual probiotics. Probiotics improve water quality while reducing pathogenic bacteria. Probiotics show positive effects through an improvement in the physiological and immune responses of shrimps. Probiotics are increasingly becoming important and more common in any organic shrimp farming.